2002
DOI: 10.1002/1521-3951(200207)232:1<71::aid-pssb71>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of Fibonacci Quasi-Periodic Heterostructures

Abstract: 73.21.Fg We study the electronic states of GaAs-AlAs Fibonacci heterostructures grown along the (001) direction. We employ an empirical tight-binding Hamiltonian including spin-orbit coupling together with the surface Green's function matching method. We present results for the L point of the finite eighth Fibonacci generation. We compare these results with those of the constituent quantum wells. No Fibonacci spectrum is found in the energy regions studied, but broad bands with different spatial localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Experimental as well as theoretical studies of these superlattices are concentrated on the consequences of the long-range correlations induced by the aperiodic arrangement at a length scale longer than atomic one [24,25]. In particular, this problem has been extensively investigated in the Fibonacci superlattices which are regarded as a typical example of aperiodic systems [26,27,28]. In these studies, it has been found that the wave functions of one-particle states are critical, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental as well as theoretical studies of these superlattices are concentrated on the consequences of the long-range correlations induced by the aperiodic arrangement at a length scale longer than atomic one [24,25]. In particular, this problem has been extensively investigated in the Fibonacci superlattices which are regarded as a typical example of aperiodic systems [26,27,28]. In these studies, it has been found that the wave functions of one-particle states are critical, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Merlin et al [2] were the first to grow a Fibonacci lattice of GaAs and AlAs and they studied its x-ray diffraction and Raman scattering properties. Since then, many other interesting studies of propagation of electrons, electromagnetic waves and acoustic waves have been reported in quasiperiodic multi-layered onedimensional structures with several profiles like those of Fibonacci, Cantor, Rudin-Shapiro, Thue-Morse, and others [3][4][5]. Of particular interest is the understanding of the optical propagation, localization and transmission of optical waves in this type of structures, which are different from the periodic or random structures due to the long correlation effects induced by the quasiperiodicity [6].…”
Section: Introductionmentioning
confidence: 99%
“…These multilayers may have promising technological applications in non-linear optics as well as in the design of optical devices like soft x-ray filters, efficient photovoltaic solar cells [6][7][8], etc. In this work we propose a model for a new aperiodic multilayer whose refractive index is modulated by a deterministic numerical 3 Author to whom any correspondence should be addressed. sequence named 'the 1s-counting sequence', formed by the number of 1s in the binary representation of the natural numbers [9].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies of propagation of electrons, electromagnetic waves and acoustic waves in quasi-periodic multilayered one-dimensional structures with several profiles like those of Fibonacci, Cantor, Rudin-Shapiro, Thue-Morse, etc. [6][7][8]. The numerical sequence formed by the quantity of odd numbers in each row of the Pascal's Triangle, has the property of self-similarity.…”
mentioning
confidence: 99%